Menuju Pengauditan Holistik dengan Pendekatan Yin dan Yang: Upaya Meningkatkan Relevansi - Wartono, Wartono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2006)
The paper aims at revealing the rigidity or the fetter in the auditors in carrying out the auditing against accounting report. The rigidity becomes a main cause of lowered relevancy of audited report utility for the user. Next, â€œYin and Yangâ€ holistic approach facilitates the emergence of something unrecognized by the auditor, but mainly acknowledge by the user of audited report, into the surface as the audit objective. Throughout the mix of â€œYinâ€ and â€œYangâ€ within auditing, result relevancy improves and accountant profession provides the necessary utility.Keywords: Holistic Auditing, Yin and Yang, Relevancy